It’s barcoding Jim, but not as we know it - Cruickshank, Robert H.; Munck, Lars (Zootaxa, 2011)
It has long been the dream of many ecologists that one day it will be possible to use a hand-held machine to identify biological specimens in the field (e.g. Janzen 2004). An analogy has been made with the so-called “tricorder” from the popular science fiction televison series Star Trek (Savolainen et al. 2005). This idea has arisen largely from the DNA barcoding community, who promote the use of a single universal DNA sequence (usually the mitochondrial cytochrome oxidase I (COI) gene) for species identification (Hebert et al. 2003). Such a device is typically imagined as using DNA as the basis for species determination. However, critics of this idea (e.g. Cameron et al. 2006) have argued that a DNA-based device would be impractical as tissue samples would need to be obtained as a source of DNA, which would necessitate handling the specimen. This suggests that the tricorder may not be such a good analogy; whereas, in Star Trek, the crew of the USS Enterprise merely had to point their tricorders at the organism in question, in reality, field-workers using a DNA-based system would have to obtain a tissue sample and load it into the machine in order to identify their specimen (Cameron et al. 2006, p.844).